Using a Delphi consensus process to develop an acupuncture treatment protocol by consensus for women undergoing Assisted Reproductive Technology (ART) treatment - Smith, Caroline A (BioMed Central, 2012)
BACKGROUND: Assisted reproductive technologies (ART) are increasingly utilised for resolving difficulties conceiving. These technologies are expensive to both the public purse and the individual consumers. Acupuncture is widely used as an adjunct to ART with indications that it may assist reducing the time to conception and increasing live birth rates. Heterogeneity is high between treatment protocols. The aim of this study was to examine what fertility acupuncturists consider key components of best practice acupuncture during an ART cycle, and to establish an acupuncture protocol by consensus. METHODS: Fifteen international acupuncturists with extensive experience treating women during ART interventions participated in 3 rounds of Delphi questionnaires. The first round focused on identifying the parameters of acupuncture treatment as adjunct to ART, the second round evaluated statements derived from the earlier round, and the third evaluated specific parameters for a proposed trial protocol. Consensus was defined as greater than 80% agreement. RESULTS: Significant agreement was achieved on the parameters of best practice acupuncture, including an acupuncture protocol suitable for future research. Study participants confirmed the importance of needling aspects relating to the dose of acupuncture, the therapeutic relationship, tailoring treatment to the individual, and the role of co-interventions. From two rounds of the Delphi a consensus was achieved on seven treatment parameters for the design of the acupuncture treatment to be used in a clinical trial of acupuncture as an adjunct to ART. The treatment protocol includes the use of the traditional Chinese medicine acupuncture, use of manual acupuncture, a first treatment administered between day 6–8 of the stimulated ART cycle which is individualised to the participant, two treatments will be administered on the day of embryo transfer, and will include points SP8, SP10, LR3, ST29, CV4, and post transfer include: GV20, KD3, ST36, SP6, and PC6. Auricular points Shenmen and Zigong will be used. Practitioner intent or yi will be addressed in the treatment protocol. CONCLUSIONS: Despite a lack of homogeneity in the research and clinical literature on ART and acupuncture, a consensus amongst experts on key components of a best practice treatment protocol was possible. Such consensus offers guidance for further research.